The impact of recurrent gestational diabetes on maternal metabolic and cardiovascular risk factors. (14th December 2012) - Winhofer, Yvonne; Tura, Andrea; Prikoszovich, Thomas; Winzer, Christine; Schneider, Barbara; Pacini, Giovanni; Luger, Anton; Kautzky‐Willer, Alexandra
Abstract Objective The development of overt diabetes in women with prior gestational diabetes mellitus (priorGDM) has been linked to several risk factors including age, obesity and insulin therapy during pregnancy; the role of recurrent GDM as a further risk factor remains unclear. As studies examining detailed metabolic consequences of recurrent GDM are missing and the role of recurrent GDM on cardiovascular risk is unknown, our aim was to investigate the impact of recurrent GDM (within 5 years after an index pregnancy) on metabolic and cardiovascular parameters. Methods Oral and intravenous glucose tolerance tests as well as assessment of cardiovascular risk factors were performed at baseline (6 months after index pregnancy) and 5 years thereafter in 21 prior GDM with recurrent GDM (recGDM), 41 prior GDM with no additional pregnancy (nonrecGDM) and 10 healthy controls [CON]. Results Despite weight gain in recGDM (2·3 ± 5·1 vs. −1·3 ± 6·7 kg, P < 0·04), glucose tolerance, insulin sensitivity and secretion did not differ compared with nonrecGDM at baseline and follow‐up. Furthermore, recGDM did not exhibit increased cardiovascular risk factors. Metabolic deterioration in (19% of) the total priorGDM group was associated with decreased insulin sensitivity (OGIS:367·4 ± 89·6 vs. 436·4 ± 75·5 mL/min*m², P = 0·01), hyperinsulinaemia (TIS:37·9 ± 9·7 vs. 28·0 ± 10·2 nM, P < 0·006) and postchallenge hyperglycaemia at 5 years postpartum. Conclusions Recurrence of gestational diabetes was not associated with deterioration of glucose metabolism, insulin sensitivity and secretion nor with increased cardiovascular risk. Consequently, priorGDM should not be recommended to refrain from subsequent pregnancies, but be encouraged to regain and maintain normal body weight after delivery and regularly undergo OGTTs to early detect metabolic deterioration.